The Rational Distance Problem for Equilateral Triangles - Barbara, Roy; Karam, Antoine (Communications in Mathematics and Applications, 2018)
We provide a complete characterization of all equilateral triangles \(T\) for which there exists a point in the plane of \(T\), that is at rational distance from each vertex of \(T\).